Evaluating the effectiveness of employee assistance programmes: a systematic review. Issue 1 (2nd January 2018) - Joseph, Beulah; Walker, Arlene; Fuller-Tyszkiewicz, Matthew
ABSTRACT: The rapid growth of employee assistance Programmes (EAPs) has not been matched by the accompanying research base of their efficacy. Given the inconsistent information relating to the effectiveness of EAPs in enhancing employee and organizational outcomes, the present review systematically appraised available evidence from organizational psychology and business databases and grey literature sources. A total of 17 studies examining the impact of EAPs, met the inclusion criteria. These were mostly from North America and utilized quantitative methodology and pre- and post-intervention designs. The majority of studies focused on EAPs offered by external providers and the counselling service, with the most common limitations being discrepancies in variable definitions and an absent comparable control group. Overall, this review found that utilizing EAPs enhanced employee outcomes, specifically improving levels of presenteeism and functioning. Absenteeism was most commonly investigated but produced mixed results. Presenteeism demonstrated a stronger effect size and greater improvement than absenteeism, suggesting presenteeism as a better variable for assessing EAP effectiveness. This review clarified parameters of existing evidence and highlighted the narrow range of measures used to date, omitting important constructs such as health and well-being and productivity. A broader evaluation capturing a wider range of variables is urgently needed.